THE EFFECT OF VIDEO-ASSISTED PROBLEM BASED LEARNING MODEL ON STUDENTS’ LEARNING OUTCOMES ON INDONESIAN ECOLOGY AND BIODIVERSITY TOPIC - Indah, Dara Puspa; Oktavia, Rani; Arif, Khairil; Putri, Azza Nuzullah (SEMESTA: Journal of Science Education and Teaching, 2024)
This research .was based on the results of a preliminary study conducted at SMPN 16 Padang, which showed that students' cognitive learning outcomes were still not optimal in science learning. This research aims to determine the influence of the video-assisted Problem Based Learning (PBL) model on learning outcomes for Indonesian Ecology and Biodiversity Material. This type of research is a quasi experiment with a non equivalent control group design research design. The population in this study were all the 7th grader at SMPN 16 Padang. Sampling used purposive sampling technique. So we obtained one experimental class by applying the video-assisted Problem Based Learning model, namely class VII.6 and one control class with the conventional learning model, namely class VII.7. Data collection was carried out through pre-test and post-test. The data obtained were analyzed using inferential statistical analysis and the results obtained from the similarity test of the two pre-test and post-test averages were respectively 0.067 for the pre-test sig, and 0.000 for the post-test sig, which means that H0 is rejected or there is a significant difference in both classes because sig < 0.05. Thus, it can be concluded that there is a significant influence of the application of the video-assisted PBL model on the learning outcomes of Indonesian ecology and biodiversity material.